1982
DOI: 10.2172/6588943
|View full text |Cite
|
Sign up to set email alerts
|

Final report - Magma Energy Research Project

Abstract: Distribution Category UC-66

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The resulting core (<20% recovery) was analyzed by Macdonald and Katsura [1961] and Richter and Moore [1966]. Later drilling operations carried out by the USGS in 1967USGS in , 1975USGS in , 1976USGS in , 1979USGS in , 1981USGS in , and 1988 [Colp, 1982;Hardee, 1988]. All 23 holes penetrated the thickening upper crust (Figure 3b), several of the later holes passed through the thermal maximum, and three passed completely through the partially molten core of the lake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting core (<20% recovery) was analyzed by Macdonald and Katsura [1961] and Richter and Moore [1966]. Later drilling operations carried out by the USGS in 1967USGS in , 1975USGS in , 1976USGS in , 1979USGS in , 1981USGS in , and 1988 [Colp, 1982;Hardee, 1988]. All 23 holes penetrated the thickening upper crust (Figure 3b), several of the later holes passed through the thermal maximum, and three passed completely through the partially molten core of the lake.…”
mentioning
confidence: 99%
“…defined the edges of the magma layer to be near nails N11 and S7 along the minor axis of the lake, and nails 7 and 29 along the major axis in 1976 (refer toFigure 3). In 1980 the boundaries were near N9 and S5 [Herrnance andColp, 1982], suggesting an overall shrinking inward of the conductive magma lens, although no change was detected near the western end of the lake.Comparison of Geophysical Results to Direct GeologicalObservations Four factors are expected to have major effects on seismic velocity within the lava lake: temperature, fracture presence and content, melt presence, and vesicle presence within the melt. Temperature dependence of seismic velocity in solid basalts has been studied empirically [e.g., Murase and McBirney, 1973; Kroenke et al, 1976], although results are uncertain for temperatures just below the solidus.…”
mentioning
confidence: 99%
“…The Magma Energy project of the U.S. Department of Energy began in the summer of 1973 with a proposal to the Atomic Energy Commission that the magma energy concept be studied as an alternative energy technology (Colp, 1982 Department of Energy. Total funds expended over these years amounted to $ 4 .…”
Section: Project Historymentioning
confidence: 99%
“…In addition, field investigations were pursued in and around the Kilauea Iki lava lake, a pit crater filled with lava from the 1 9 5 9 eruption of Kilauea Volcano, Hawaii. These investigations included seismic and electrical experiments to detect the presence of melt, temperature measurements, and petrologic analysis of cores recovered from small-scale drilling experiments (Colp, 1982 The experiments demonstrated that high rates of energy extraction could be achieved and that the effective heat transfer area in the magma zone could be increased with time as the zone solidified and thermally fractured (Dunn, 1981;Hardee et al, 1981).…”
Section: Project Historymentioning
confidence: 99%